PENGARUH LITERASI EKONOMI, GAYA HIDUP, KONFORMITAS, DAN MODERNITAS TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS LAMPUNG - Winda Hasanah; Nurdin Nurdin; Rahmawati Rahmawati (FKIP Universitas Lampung, 2019)
This research aims to determine the influence of social economic literacy, lifestyle, conformity, modernity towards consumptive behavior economic education students lampung university. The method used in this study is descriptive verification with ex post facto approaches and surveys. The sample in this research used an entire population of 67 students. Data collection using interview, observations, test, and questionnaire. Partial hypothesis testing using the t test, while simultaneous testing using the f test. Based on the result of the analysis, it was conclude that there was a partial effect between economic literacy, lifestyle, conformity, modernity towards consumptive behavior economic education students lampung university. Simultaneously there is also effect between economic literacy, lifestyle, conformity, modernity towards consumptive behavior economic education students lampung university. Calculated f value of 61,591 with a significance of 0,000.